CITRA DIRI REMAJA DALAM PERSPEKTIF TEOLOGI - Galuh Pandandari (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2018)
The goal of this writing is to describe theological perspective of youth self image and to elaborate factors that influence its forming in order to find strategic principles in the youth ministry. Human being is created in perfect self image based on God’s image. This self image is totally corrupted when man fell into the sin. A positive self image of youth should be built up starting from the renewing in Christ. Further, are the roles of the church and the authoritative figures around the youth most decisive in forming a positive self image of the youth. I recommend, as writer, to the church and adult people around the youth to use strategic principles in the youth ministry.